2001
DOI: 10.1161/01.atv.21.5.797
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Signal Transduction Cascade, a Novel Pathway for the Regulation of Endothelial Nitric Oxide Production in Coronary Blood Vessels

Abstract: Abstract-The aim of this study was to determine whether cAMP signal transduction plays a role in the regulation of endothelial nitric oxide (NO) production. Canine coronary blood vessels were isolated, and nitrite, the hydration product of NO, from these vessels was quantified by using the Griess reaction. Forskolin (10 Ϫ4 mol/L), 8-bromo-cAMP (10 Ϫ2 mol/L), or isoproterenol (10 Ϫ4 mol/L) significantly increased nitrite release to 168Ϯ10, 162Ϯ13, or 149Ϯ13 pmol/mg, respectively, from isolated coronary microves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 48 publications
6
44
0
Order By: Relevance
“…Therefore, it is suggested that PKA-dependent eNOS phosphorylation provides a compensatory mechanism for the enzyme activation without involving intracellular Ca 2+ increase. In consistent with this notion, a critical role of PKA in vascular nitric oxide production as a compensatory mechanism has also been demonstrated previously in coronary blood vessels (Zhang and Hintze, 2001). …”
Section: Pka Regulates Enos Activity In Response To Shear Stresssupporting
confidence: 86%
“…Therefore, it is suggested that PKA-dependent eNOS phosphorylation provides a compensatory mechanism for the enzyme activation without involving intracellular Ca 2+ increase. In consistent with this notion, a critical role of PKA in vascular nitric oxide production as a compensatory mechanism has also been demonstrated previously in coronary blood vessels (Zhang and Hintze, 2001). …”
Section: Pka Regulates Enos Activity In Response To Shear Stresssupporting
confidence: 86%
“…Blockade or insufficient AM cross-talk between endothelial cells through juxtacrine loops mediated by laterally expressed EndoCL might contribute to hyperpermeability of the endothelial monolayer in response to stress stimuli, such as polymorphonuclear-leukocyte-derived oxygen metabolites (Hippenstiel et al, 2002). Apically expressed EndoCL might mediate endothelium-dependent AM-induced vasodilatation (Hinson et al, 2000;Zhang and Hintze, 2001). Similarly, EndoCL could be important in mediating CGRP-mediated proliferation (Haegerstrand et al, 1990) and migration (present study) of endothelial cells.…”
Section: Discussionmentioning
confidence: 62%
“…NOS can also be activated through the adenylyl cyclase/ PKA pathway. 24,25 Therefore, the short-term effect of aldo- sterone on the adenylyl cyclase/PKA pathway in ECs was assessed. Aldosterone (10 pmol/L to 10 nmol/L) had no effect on isoproterenol-, forskolin-, or cAMP-mediated PKA activity (data not shown).…”
Section: Assessment Of Potential Mechanisms Responsible For Aldosteromentioning
confidence: 99%